2003
DOI: 10.1007/s00148-003-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

The school-to-work transition of 2 nd generation immigrants in Denmark

Abstract: 2 nd generation immigrants from less developed countries have less education and a lower employment frequency compared to the native Danish youth. We analyse the school-to-work transition of these groups using panel data for the years 1985–1997. The educational gap between 2 nd generation immigrants and the Danish youth is to some extent explained by age structure, while age does not explain the native-immigrant gap concerning the duration of waiting time until first job and the duration of first employment sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 11 publications
5
105
0
3
Order By: Relevance
“…The work by Card andcollaborators (2000, 2005), using similar methods, also found substantial links between immigrant parents and their U.S. Across a number of countries, studies using aggregate data have consistently found much higher estimates of transmission than those using comparable micro-/family-level data. At the same time, intergenerational associations are consistently lower in migrant than in nonmigrant families (Aydemir et al 2013;Bauer and Riphahn 2006;Borjas 1992;Dustmann 2008;Gang and Zimmermann 2000;Nielsen et al 2003;Riphahn 2003). 2 Two recent studies, an OECD review of intergenerational mobility studies by d 'Addio (2007:57) and Dustmann and Glitz (2011), noted the discrepancies in different estimates but did not address the source of the differences.…”
Section: Methodsological Implications Of Group-level Variation In Thementioning
confidence: 99%
“…The work by Card andcollaborators (2000, 2005), using similar methods, also found substantial links between immigrant parents and their U.S. Across a number of countries, studies using aggregate data have consistently found much higher estimates of transmission than those using comparable micro-/family-level data. At the same time, intergenerational associations are consistently lower in migrant than in nonmigrant families (Aydemir et al 2013;Bauer and Riphahn 2006;Borjas 1992;Dustmann 2008;Gang and Zimmermann 2000;Nielsen et al 2003;Riphahn 2003). 2 Two recent studies, an OECD review of intergenerational mobility studies by d 'Addio (2007:57) and Dustmann and Glitz (2011), noted the discrepancies in different estimates but did not address the source of the differences.…”
Section: Methodsological Implications Of Group-level Variation In Thementioning
confidence: 99%
“…As stated in the previous research, both national and international research on the labour market position for the descendant generation shows that, in terms of employment rates and wages, descendants are worse off in the labour market than the native population (Algan et al 2009;Belzil & Poinas 2008;Chiswick & DebBurman 2003;Hammarstedt 2002Hammarstedt , 2009Rooth & Ekberg 2003;Skyt Nielsen et al 2001;Tu 2010). In this perspective, it is interesting to see that with regard to occupational mismatch, there is little (the male population) or no (the female population) difference between the descendant generation and the reference group (Swedish born with two Swedishborn parents).…”
Section: Resultsmentioning
confidence: 70%
“…Algan et al (2009) found that in France, Germany and the UK, 'there is a clear indication that -in each country -labour market performance of most immigrant groups as well as their descendants is -on average worse than that of the native population, after controlling for education, potential experience and regional allocation' [Algan et al 2009: 24. For Denmark see Skyt Nielsen et al (2001); for France, Belzil & Poinas (2008); for the US, Chiswick & DebBurman (2003); and for Canada, Tu (2010)]. …”
Section: Theory and Earlier Researchmentioning
confidence: 99%
“…The main conclusion of this literature is that the second generation cannot be considered as one homogeneous group and that the intergenerational transmission of labour market outcomes, human capital attainment, parental education, and neighbourhood effects are crucial determinants of the labour market position of immigrant children (For the US: Aydemir and Sweetman (2006); Card (2005); for Scandinavian countries: Behtoui (2004); Jakobsen and Smith (2003); Nielsen et al (2003); Van Ours and Veenman (2003)). …”
Section: Empirical Evidencementioning
confidence: 99%